Gravity stabilized drainage in porous media with controlled disorder - Khobaib Khobaib; Paula Reis; Marcel Moura; Renaud Toussaint; Eirik Grude Flekkøy; Knut Jørgen Måløy (Physical Review Research)
This work presents an experimental, numerical, and theoretical investigation of slow drainage processes in porous media, focusing on systematic variations in pore-scale disorder. We examine a system comprising a monolayer of cylinders in a quasi-two-dimensional (2D) geometry, where the medium's disorder is controlled via a disorder parameter, ε. By systematically altering ε, we randomly shift the positions of the cylinders and analyze the resulting effects on the gravity stabilized invasion front. Our results show that increasing ε has a significant impact on the stable width of the invasion front, with this width scaling with the disorder parameter according to an exponent β=0.57, which closely matches the theoretical value predicted by percolation theory for 2D systems. Additionally, we derive a reciprocal relationship between the dimensionless fluctuation number and the disorder parameter ε. Moreover, we find a correlation between the invasion front width and the size of trapped clusters in the system, and we explore how pore disorder affects the air saturation left behind the invasion front. Both our experimental and numerical findings exhibit exponent values that align with theoretical scaling predictions. This study advances the current understanding of multiphase flows in porous media by specifically addressing the influence of pore-scale disorder on the morphology of invasion fronts.